Malignant solitary fibrous tumor occurring in the mediastinal pleura showing NAB2ex4‐STAT6ex2 fusion and negative STAT6 immunohistochemistry: A case report - Zhang, Peng (Thorac Cancer, 2020)
Solitary fibrous tumor (SFT) is a rare clinical tumor, defined as a mesenchymal tumor of fibroblastic origin. A classic SFT is benign in most cases, but its clinical behavior is unpredictable. Lately, molecular analyses has discovered that almost all SFTs harbor an NAB2‐STAT6 fusion gene, which is considered specific to this tumor type. Recent studies have suggested that nuclear STAT6 immunoreactivity is a highly sensitive and specific marker of SFTs and can be helpful when diagnosis is inconclusive by conventional methods. We herein report the case of a rare malignant solitary fibrous tumor occurring in the mediastinal pleura. An 82‐year‐old Chinese man with intermittent breathlessness was referred to our hospital. Chest CT showed a significantly enhanced irregular huge soft tissue mass in the anterior mediastinal area. After radical resection, the immunohistochemistry staining results of the sample showed that STAT6 was negative. The final diagnosis was confirmed by qualitative endpoint reverse transcriptase‐polymerase chain reaction technique, showing positive NAB2ex4‐STAT6ex2 fusion.